THE SPATIALITY OF INTERSECTION: A POSTCOLONIAL APPROACH OF POPULAR ECONOMY IN ARGENTINA - Palumbo, María Mercedes (2020)
This article aims to identify the contributions of Partha Chatterjee’s postcolonial approach to the understanding of contemporaneous popular economy in Argentina as a spatiality of intersection. As a theoretical inquiry, the outlined reflections were elaborated based on a theoretical-empirical research, currently in progress, following a qualitative methodological strategy. The results indicate the analytical productivity of the postcolonial approach in the study of everyday practices, subjects and demands for rights within popular economy.